Correlation between Polypharmacy and Length of Stay Geriatric Patient in Mohammad Hoesin Palembang Hospital - Tanzil, Iswadi; Riviati, Nur; Saleh, Irsan (UI Scholars Hub, 2021)
Introduction. Geriatric patients have multipathological characteristics, low physiologic reserves, atypical clinical signs and symptoms, decreased functional status, and nutritional disturbances. This situation is a risk factor for polypharmacy. Polypharmacy is closely related to drug side effects, drug interactions, and patient compliance. Polypharmacy is thought to have a relationship with the length of stay in geriatric patients. The purpose of this study was to determine the correlation between polypharmacy and length of stay in geriatric patients at Moehammad Hoesin Hospital Palembang. Methods. This was a cross-sectional study with a correlation test design conducted at Dr. Mohammad Hoesin Hospital (RSMH) Palembang from April 2021 to July 2021. The sample was geriatric patients aged > 60 years. We collected data on the number and types of drugs given and the length of hospitalization. All data processing and analysis in this study were conducted by using SPSS version 22 for Windows. Results. Of 56 geriatric patients, there was 28 female (50%) and 28 male (50%). The median value of the number of drugs was 7 (3-32). Patients without polypharmacy were 7 (12.5%), and patients with polypharmacy were 49 (87%). The median length of hospitalization for geriatric patients at RSMH was 11.5 (range 1-47) days. There was a correlation between polypharmacy and length of stay (r=0.277; p value=0.039). Conclusion. There is a weak correlation between polypharmacy and length of stay (r=0.277; p=0.039).